Organizational commitment to mediate workload and compensation on work productivity at Madina Bukittinggi Hospital - Ramadhi Ramadhi; Kiki Sarianti; Yolanda Desti (Junal Ilmu Manajemen, 2023)
Observations by researchers in the field found that there were employee complaints regarding the workload and compensation carried out at Madina Bukittinggi Hospital and a lack of organizational commitment, causing a decrease in employee work productivity at Madina Bukittinggi Hospital, so it is necessary to conduct research on the effect of workload and compensation on work productivity through employee commitment as a mediating variable. This study consists of three independent variables, namely workload and compensation and one variable of work productivity and job satisfaction as an intervening variable. The analytical method used is path analysis. The method of data collection in this study was to use a questionnaire filled out by respondents, namely employees of the Madina Bukittinggi Hospital. The results obtained based on the Partial Test (t test) obtained: there is a significant effect of workload on organizational commitment, there is a significant effect of compensation on organizational commitment, there is a significant effect of workload on work productivity, there is a significant effect compensation on work productivity, there is a significant effect of organizational commitment on work productivity, organizational commitment cannot mediate the effect of workload on work productivity, organizational commitment cannot mediate the effect of compensation on work productivity.